2005
DOI: 10.1089/jwh.2005.14.441
|View full text |Cite
|
Sign up to set email alerts
|

Living in Fear of Experiencing Physical and Sexual Abuse Is Associated with Severe Depressive Symptomatology among Young Women

Abstract: Not only the direct lifetime experience of abuse but also the presence of fear of abuse is associated with severe depressive symptomatology among young women. Fear of abuse is also an important factor to take into consideration in assessing young women with depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This is consistent with other literature on women's experiences of abuse. In a study of women ages 15 to 24, Csoboth, Birkás, and Purebl (2005) demonstrated a relationship between experiencing fear in daily life and a history of abuse either directly, such as by a partner, or indirectly, such as seeing one parent abuse the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other literature on women's experiences of abuse. In a study of women ages 15 to 24, Csoboth, Birkás, and Purebl (2005) demonstrated a relationship between experiencing fear in daily life and a history of abuse either directly, such as by a partner, or indirectly, such as seeing one parent abuse the other.…”
Section: Discussionmentioning
confidence: 99%
“…It has, however, has been shown to be an important predictor of mental health symptoms and engagement in health-promoting behaviors in adolescent female populations (Raiford, Diclemente, & Wingood, 2009) and in populations of formerly abused adult women (Csoboth, Birkás, & Purebl, 2005). Greater understanding of the role, persistence, and effects of fear among young women who have experienced adolescent dating abuse will allow nurses to identify how and when these women may be experiencing fear related to such experiences and thus provide more comprehensive, supportive mental health care to these women.…”
mentioning
confidence: 99%
“…Research and clinical literature demonstrate that women who undergo physical or sexual abuse have a history of more suicide attempts and self-inflicted injury than women who were not victims of violence (Etzel, 2006;MaKeganet, Neale, & Robertson, 2005;Maniglio, 2011) a higher tendency to develop eating disorders (Franko & Keel, 2006;Treuer, Koperdak, Rozsa, & Furedi, 2005), a higher frequency of addictive drug use (Segal, 2001;Somer, 2003;Zickler, 2002), somatic disorders (Ullman & Brecklin, 2003) and depression (Csoboth, Birkas, & Purebl, 2005), more dissociative symptoms (Somer, 2003;Sta & Elaine, 2005) and signs of PTSD (Filipas & Ullman, 2006;Sharhabani-Arzy, Amir, Kotler, & Liran, 2003). Moreover, they suffer from a negative body image and low self-esteem (Eubanks, Kenkel, & Gardner, 2006) as well as more borderline personality disorders (Lobbestael, Arntz, & Bernstein, 2010) than women with no history of abuse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2008b); witnessing family violence (Sox 2004); level of participation in religious activities (Helm et al . 2002); assumptions and beliefs of women such as self‐control, self‐worth and control of event's outcomes (Harris & Valentiner 2002); and experiences of domestic violence (Csoboth et al . 2005, Mezey et al .…”
Section: Introductionmentioning
confidence: 99%